Determination Of The Motor Development Levels Of 9-10 Years Old Children - İbrahim Şahin; Mustafa Gürker Tepe; Tolga Kalebozan (Türk Spor ve Egzersiz Dergisi, 2020)
The aim of this research was to observe the level of motor development of a group of students aged 9-10. Ninety-three students (42 girls, 51 boys) from the TAF Mehmetcik Foundation Hafize İhsan Payaza Primary School have voluntarily attended the research from Çankaya District in Ankara, Turkey. The children who were in the experimental group had the sub-tests of Test of Gross Motor Development-2 (TGMD-2); Manipulative skills and object control skill tests and each of them was graded. For each activity of the tests, 1 point was given if the students were successful and 0 points if not. At the end of the grading of each trial, total grades ached for each activity. Total grades were calculated for each skill and the status was defined. The result of this study will be useful for the students who have completed the basic Movement period of Psycho-motor development phases and who are in the last phase of sportive Movements period of Specific activity skills aged 7-10 years to define their basic motor features and to be guided to the correct sport branches. On one hand, it is aimed to help develop the normative values for the Turkish children using the TGMD-2 which was adapted from the test which is widely used in scientific researches while on the other hand, the development of basic motor properties based on anthropometric characteristics will be able to observe.